(untitled) (Cambridge UK, 2001)
This handbook presents the current state of practice, method and understanding in the field of mathematical finance. Each chapter, written by leading researchers, starts by briefly surveying the existing results for a given topic, then discusses more recent results and, finally, points out open problems with outlines for possible solutions.
Keywords: Risk management,Phái sinh (Tài chính),Derivative securities,Quản lý rủi ro; Mô hình toán học,Mathematical models